2011
DOI: 10.1002/ar.21283
|View full text |Cite
|
Sign up to set email alerts
|

Metformin Induces G1 Cell Cycle Arrest and Inhibits Cell Proliferation in Nasopharyngeal Carcinoma Cells

Abstract: It has been reported that metformin, a biguanide derivative widely used in type II diabetic patients, has antitumor activities in some cancers by activation of AMP-activated protein kinase (AMPK). But its role in nasopharyngeal carcinoma (NPC) is not known. Here, we reported for the first time that 1-50 mM of metformin in a dose-and time-dependent manner suppressed cell proliferation and colony formation in NPC cell line, C666-1. Further studies revealed that the protein level of cyclin D1 decreased and the pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 34 publications
2
14
0
Order By: Relevance
“…However, metformin's specific anticancer mechanism has not been clarified. Some studies suggest that metformin can activate the tumor suppressors in the AMPK metabolic pathway and prompt downstream factors such as mTOR, p53, and FOXO3 to adjust metabolism, growth rate, and the cell cycle . Our results confirmed that a combination of sorafenib and metformin upregulated the activity of AMPK and expression of TIP30.…”
Section: Discussionsupporting
confidence: 81%
“…However, metformin's specific anticancer mechanism has not been clarified. Some studies suggest that metformin can activate the tumor suppressors in the AMPK metabolic pathway and prompt downstream factors such as mTOR, p53, and FOXO3 to adjust metabolism, growth rate, and the cell cycle . Our results confirmed that a combination of sorafenib and metformin upregulated the activity of AMPK and expression of TIP30.…”
Section: Discussionsupporting
confidence: 81%
“…Lin et al (8), Luo et al (38) and Sikka et al (39) demonstrated accumulation of cells in the G0/G1 phase when HNSCC cell lines were treated with metformin. Activation of AMPK and subsequent inhibition of mTORC1 signaling, reduction of cyclin D1 levels and dephosphorylation of AKT (at Ser473) have been shown to participate in metformin-induced apoptotic process (69). …”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we have documented that metformin diminishes cyclin D1 expression, replenishes p53 expression and induces apoptosis in HeLa cells (Figure 1-3). Reduction of cyclin D1 expression is also found in nasopharyngeal cancer (C666-1), prostate cancer (LNCaP) and head and neck squamous cell carcinoma (FaDU and Detroit 562) incubated with 5-20 mM metformin for 72 h (Sahra et al, 2008;Zhao et al, 2011;Sikka et al, 2012). Another study shows that metformin plays an important role in global inhibition of protein translation, including cyclin D1 protein (Sikka et al, 2012).…”
Section: Discussionmentioning
confidence: 92%